Autonomous tractor to plough and harvest within a laser perimeter - Ekram, S.M.A.; Kader, Md. Mobin; Shahera, Fatema tuz; Shirmin, Nusrat (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.